Differences in Evolution of Epileptic Seizures and Topographical Distribution of Tissue Damage in Selected Limbic Structures Between Male and Female Rats Submitted to the Pilocarpine Model - Matovu, Daniel; Cavalheiro, Esper A. (Frontiers in Neurology, 2022)
Epidemiological evidence shows that clinical features and comorbidities in temporal lobe epilepsy (TLE) may have different manifestations depending on the sex of patients. However, little is known about how sex-related mechanisms can interfere with the processes underlying the epileptic phenomenon. The findings of this study show that male rats with epilepsy in the pilocarpine model have longer lasting and more severe epileptic seizures, while female rats have a higher frequency of epileptic seizures and a greater number of seizure clusters. Significant sex-linked pathological changes were also observed: epileptic brains of male and female rats showed differences in mass reduction of 41.8% in the amygdala and 18.2% in the olfactory bulb, while loss of neuronal cells was present in the hippocampus (12.3%), amygdala (18.1%) and olfactory bulb (7.5%). Another important gender-related finding was the changes in non-neuronal cells with increments for the hippocampus (36.1%), amygdala (14.7%) and olfactory bulb (37%). Taken together, our study suggests that these neuropathological changes may underlie the differences in the clinical features of epileptic seizures observed in male and female rats.